Suboptimal biventricular pacing. What is the mechanism?. Issue 4 (1st June 2019) - Tan, Vern Hsen; Yeo, Colin; Wong, Kelvin
Abstract: Suboptimal biventricular pacing has deleterious effects on patients with cardiac resynchronization therapy. We describe a unique case of suboptimal biventricular pacing and our approach to overcome it.